SYSTEM OF EDUCATION OF DOCTORS IN TERMS OF THE FORMATION OF THEIR PROFESSIONAL COMPETENCE IN THE FIELD OF FORENSIC SCIENCE NECESSARY FOR REACHING OBJECTIVES IN CRIMINAL PROCEEDINGS - I. V. Panchenko; I. O. Perepechina (Исследования и практика в медицине, 2015)
The article deals with the problem of education of doctors in order to form their competence in the field of forensic medicine, necessary in case to carry out further the procedural role of a specialist in the field of forensic medicine or a forensic medical expert. The differences in the systems of their education, as well as distinction between the systems of training of forensic medical experts and forensic experts in other fields of knowledge are shown.